Effect of Polyethylene Glycol on the NiO Photocathode - Shengjun Li; Zeng Chen; Wenping Kong; Xiyang Jia; Junhao Cai; Shaokang Dong (Nanoscale Research Letters, 2017)
Abstract In this study, a uniform nanoporous NiO film, with a thickness of up to 2.6 μm, was prepared using polyethylene glycol (PEG). The addition of PEG significantly decreased the cracks in the NiO film and prevented the peeling of the NiO film from a fluorine-doped tin oxide substrate. The NiO cathode was prepared using CdSeS quantum dots (QDs) as the sensitizer, with an optimized photoelectric conversion of 0.80%. The optimized QD-sensitized NiO films were first assembled with the TiO2 anode to prepared QD-sensitized p–n-type tandem solar cells. The open circuit voltage was greater than that obtained using the separated NiO cathode or TiO2 anode.